Pengaruh Strategi Contextual Teaching And Learning (CTL) Terhadap Kemampuan Menulis Teks Biografi Siswa Kelas X SMA Negeri 2 Lintau Buo Tahun Ajaran 2021/2022 - Saberman, Aulia Rahmi BP; Rahmi, Afrini; Pebriani, Yulia (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2022)
This study aims to describe the ability to write biographical texts without, with, and how the effect of using Contextual Teaching and Learning (CTL) learning strategies on the ability to write biographical texts in class X SMA N 2 Lintau Buo. This type of research is quantitative research with experimental methods. The results of the study are described as follows. First, the students' biographical text writing skills before using the Contextual Teaching and Learning (CTL) strategy of class X students of SMA N 2 Lintau Buo with an average of 57.47. Second, students' biographical text writing skills after using the Contextual Teaching and Learning (CTL) strategy of class X students of SMA N 2 Lintau Buo with an average of 70.97. Third, the skill of writing biographical texts using Contextual Teaching and Learning (CTL) learning strategies in learning is better than before using Contextual Teaching and Learning (CTL) learning strategies. Fourth, there is a significant effect of the use of learning strategies on the skills of writing biographical texts for X grade students of SMA N 2 Lintau Buo because tcount > t table (4.32 > 1.67), so H0 is rejected and H1 is accepted. This means that there is an effect of using Contextual Teaching and Learning (CTL) learning strategies on the ability to write biographical texts for X grade students of SMA N 2 Lintau Buo. So, it can be seen that there is a significant effect between the use of Contextual Teaching and Learning (CTL) strategies on learning the skills of writing biographical texts for the tenth graders of SMAN 2 Lintau Buo.